Disseminated intravascular Coagulation in Status Epilepticus - Fischer, Sharon P.; Lee, Joseph; Zatuchni, Jacob; Greenberg, Jack (Thrombosis and Haemostasis, 1977)
Disseminated intravascular coagulation is here reported as a complication of status epilepticus. Other features of this case were rhabdomyolysis, hyperthermia, myoglobinuria and renal failure.